Nucleic acid-specific photoactivation of oligodeoxyribonucleotides labeled with deuterated dihydro-N, N, N′, N′-tetramethylrhodamine using green light - Schikora, Margot; Dutta, Subrata; Mokhir, Andriy (Histochemistry and Cell Biology, 2014)
We developed a simple protocol for high-yielding synthesis of conjugates of a deuterated dihydro-N, N, N′, N′-tetramethylrhodamine (F*) with oligodeoxyribonucleotides and a 2′-OMe RNA (a representative nuclease-resistant, chemically modified oligonucleotide) using easily accessible starting materials including NaBD and conjugates of oligonucleotides with N, N, N′, N′-tetramethylrhodamine (F). These compounds were found to be stable in air and insensitive to light at 525, 635 and 650 nm, whereas slow activation occurs upon their exposure to 470 nm light. However, at the conditions of the templated reaction, in the presence of a target nucleic acid and a photocatalyst based on the eosin structure, the F* is oxidized forming fluorescent F. This reaction is >30-fold faster than the background reaction in the absence of the template. Moreover, the presence of a single mismatch in the target nucleic acid slows down the templated reaction by eightfold. These activatable dyes can potentially find applications as nucleic acid-specific probes for super-resolution imaging in live cells. © 2014 Springer-Verlag Berlin Heidelberg.